Polyphenols and Their Anti-Obesity Role Mediated by the Gut Microbiota: A Comprehensive Review - Poblete-Aro, C (Springer, 2021)
Obesity is a global public health problem that results in chronic pathologies such as diabetes, cardiovascular diseases, and cancer. The treatment approach based on energy restriction and promotion of physical activity is ineffective in the long term. Due to the high prevalence of this pathology, complementary treatments such as brown adipose tissue activation (BAT) and white adipose tissue browning (WAT) have been proposed. Dietary polyphenols are plant secondary metabolites that can stimulate browning and thermogenesis of adipose tissue. They have also been shown to prevent body weight gain, and decrease systemic inflammation produced by high-fat diets. Ingested dietary polyphenols that reach the colon are metabolized by the gut microbiota (GM), regulating its composition and generating a great array of metabolites. GM is involved in the production of short chain fatty acids and secondary bile salts that regulate energetic metabolism. The alteration in the composition of GM observed in metabolic diseases such as obesity and type 2 diabetes can be attenuated by polyphenols. Recent studies support the hypothesis that GM would mediate WAT browning and BAT thermogenesis activation induced by polyphenol administration. Together, these results indicate that GM in the presence of polyphenols plays a fundamental role in the control of obesity possible through BAT activation. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.